Neutrophil-Lymphocyte Ratio (Nlr) And Erythrocyte Sedimentation Rate (Esr) Correlation In Covid-19 Patients At Hermina Hospital Medan - Okto PE Marpaung; Grace MK Sitorus (Jurnal EduHealth, 2022)
Background: WHO in February 2020 officially announced the name of the mysterious pneumonia as Coronavirus Disease (COVID-19). COVID-19 is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus. The Corona virus can be transmitted from human to other humans and WHO on March 12 2020 finally declared COVID-19 a global pandemic. Laboratory tests are used to determine the degree of severity so that appropriate treatment will be carried out. Purpose: This study aims to determine the relationship between the Neutrophil-Lymphocyte Ratio (NLR) and Erythrocyte Sedimentation Rate (ESR) in COVID-19 patients at Hermina Hospital Medan Method: This research is an observational correlation analytic study with a cross-sectional approach conducted at Hermina Hospital Medan against 54 research samples. Results: From this study it is known that the majority of confirmed COVID-19 patients who came to Hermina Medan Hospital were in the age group of 41-50 years and were female. The NLR value in patients with confirmed COVID-19 with the lowest score was 1.4, the highest was 46.50, and the average was 12.91. The ESR value in patients with confirmed COVID-19 with the lowest score was 10, the highest was 92, and the median was 51.12. The results showed that there was a correlation between NLR and CRP values (p = <0.001) with a low correlation strength (r = 0.354) Conclusion: A correlation was found between NLR and ESR but with a low correlation strength, so it can be concluded that the use of ESR to replace ESR value as a biomarker in COVID-19 patients is less precise